DIET FOR LIVER DISEASES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
In the current rapidly developing era, many diseases related to liver dysfunction arise due to non-compliance with dietary restrictions. Adhering to a proper diet in the early stages of these diseases should not be overlooked. Therefore, one of the most important tasks is to emphasize dietary nutrition and proper eating habits to improve liver function. Additionally, in the prevention and treatment of these diseases, increasing attention is being paid to pharmacological and artificial methods for liver treatment.